2006
DOI: 10.1093/jnci/djj299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disrupted SOX18 Transcription Factor Function on Tumor Growth, Vascularization, and Endothelial Development

Abstract: SOX18 is a potential target for antiangiogenic therapy of human cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 45 publications
3
88
0
10
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28][29][30] In fact, few studies have revealed the significance of SOX group F gene expression in human cancer, although cell line-based studies have demonstrated that both SOX 18 and SOX 7 were highly expressed in several strains of gastric, pancreatic and esophageal cancer cell lines. 22,32 In the present study, SOX group F gene expression determined by RT-PCT was increased in gastric cancer tissues than in normal gastric tissues obtained from the same individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21][22][23][24][25][26][27][28][29][30] In fact, few studies have revealed the significance of SOX group F gene expression in human cancer, although cell line-based studies have demonstrated that both SOX 18 and SOX 7 were highly expressed in several strains of gastric, pancreatic and esophageal cancer cell lines. 22,32 In the present study, SOX group F gene expression determined by RT-PCT was increased in gastric cancer tissues than in normal gastric tissues obtained from the same individuals.…”
Section: Discussionmentioning
confidence: 99%
“…22 SOX 18 expression is also reactivated during adult neovascularization associated with wound healing and tumorigenesis. 23,24 Thus, interfering with SOX 18 function, both blood vessel formation and subsequent tumor growth …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SoxF subgroup members in Drosophila and vertebrates also share highly conserved intronic positions, which represent ancient introns present before vertebrate lineage divergence (Bowles et al, 2000;Kanai et al, 1996;Taniguchi et al, 1999). Expression of mouse Sox18 across embryonic and adult tissue Northern blot analyses occurs in a very similar pattern to that of Sox7; furthermore, Sox7, Sox17, and Sox18 each colocalize to the developing mouse embryonic vasculature (Takash et al, 2001;Young et al, 2006). Functionally, Sox7 and Sox17 can also activate Sox18 targets and modify the Sox18 mutant mouse phenotype (Hosking et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At 9.5 dpc and 11.5 dpc, Sox7 is expressed in the intersomitic vessels and endothelial cells lining the posterior dorsal aorta and in the anterior neural medial axial artery (Young et al, 2006;Takash et al, 2001). At 9.5 dpc, Sox7 expression is also found in small branching vessels, throughout the embryonic vasculature, a In some tumors, such as colorectal and prostate, Sox7 down-regulation was partly due to hypermethylation at its promoter (Guo et al, 2008;Zhang et al, 2009). and in the atria (Takash et al, 2001).…”
Section: Introductionmentioning
confidence: 99%